Sustainable Living with Environmental Risks - Kaneko, Nobuhiro (Springer Nature, 2014)
Earth System Sciences; Environmental Management; Sustainable Development; Environmental Risk Management; Sustainable Society; Biodiversity and Environment; Interdisciplinary Science; Leadership Education; Sustainable Living with Environmental Risks (SLER)